Can Professional Accountant Carry out their Code of Ethics in Reporting? - Islam, Md. Rafiqul; Uddin, Md. Nasir; Ghose, Urmee (International Journal of Accounting & Finance Review, 2019)
Code of ethics is already established for professional accountant of Bangladesh in public practice and business. Every professional accountant follows this code of ethics to maintain their professionalism as well as reporting. The purpose of this research to investigate some threats those are faced by professional accountant to carry out their code of ethics. This study based on a sample of 61 professional accountants working at different audit firm and different business organization in Bangladesh. Data analyzed by using SPSS 17 and one sample statistics and one sample test was used as analytical tools in this study. There are 18 variables considered from integrity, objectivity, professional competence and due care aspect. It is found that professional accountant face various self-interest threat and self-review threat in reporting and financial report does not provide accurate information for tax purpose after audited in many cases.